Changes in physical size among Major League Baseball players and its attribution to elite offensive performance - Crotin, R. L.; Forsythe, C. M.; Bhan, S.; Karakolis, T. (The Journal of Strength and Conditioning Research, 2014)
Major League Baseball (MLB) players have not been longitudinally examined for changes in physical size. Height, weight, and body mass indices (BMIs) were examined among offensive league leaders (OLL) and MLB reference cohorts at 1970, 1990, and 2010. Anthropometric values were expected to increase successively, where OLL were expected to be larger at each respective time point. A Mixed Model analysis of variance (p < 0.05) examined anthropometric differences over time within and between groups. Mass and BMI increased over successive years with the largest effect seen between 1990 and 2010 (p < 0.001). A significant height reduction was shown for OLL from 1970 to 1990 (p < 0.05), being the only significant decrease in physical size; yet, leaders were heavier and taller compared with the MLB reference population (p < 0.014). Results show that physical size has evolved in MLB, with the OLL being the largest players shown at each year in succession. Professional baseball scouts may have been influenced by greater offensive prowess shown by larger athletes; yet, increased secular anthropometrics must also be factored in greater heights, weights, BMIs shown over time in MLB. It is possible that greater participation in strength and conditioning programs at an earlier age, advances in sport nutrition, and potential abuse of anabolic drugs are factors perpetuating growth rates at present.